1996
DOI: 10.21273/jashs.121.5.764
|View full text |Cite
|
Sign up to set email alerts
|

Relative Performance of Strawberry Cultivars from California and other North American Sources in Fumigated and Nonfumigated Soils

Abstract: Performance characteristics for eighteen strawberry cultivars (Fragaria ×ananassa), nine from California and nine from other North American sources, were evaluated in annual hill culture, with and without preplant soil fumigation (2 methyl bromide : 1 chloropicrin, 392 kg·ha -1 ). Plants grown in nonfumigated soil yielded 57% and 46% of the fruit produced by plants on adjacent fumigated soil for cultivars from California and other North American origins, respectively. Plants in nonfumigated soils also develope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…breeding programs where selections were concluded based upon growth in fumigated soils, which yielded varieties that are highly susceptible to a wealth of soilborne pathogens. While the highly methyl bromide fumigation-dependent strawberry material from the California breeding system initially yielded no obvious genetic diversity for developing cultivars adapted to sublethal effects of organisms in nonfumigated soils (Shaw and Larson 1996), tolerance to black root rot, incited by a complex of non-lethal pathogens, was detected among three genotypes released from the breeding program in Nova Scotia, Canada (Particka and Hancock 2005).…”
Section: Selection In Environments That Favor Progeny With Introgressmentioning
confidence: 99%
“…breeding programs where selections were concluded based upon growth in fumigated soils, which yielded varieties that are highly susceptible to a wealth of soilborne pathogens. While the highly methyl bromide fumigation-dependent strawberry material from the California breeding system initially yielded no obvious genetic diversity for developing cultivars adapted to sublethal effects of organisms in nonfumigated soils (Shaw and Larson 1996), tolerance to black root rot, incited by a complex of non-lethal pathogens, was detected among three genotypes released from the breeding program in Nova Scotia, Canada (Particka and Hancock 2005).…”
Section: Selection In Environments That Favor Progeny With Introgressmentioning
confidence: 99%
“…Genotype × fumigation interactions have been detected for few strawberry traits in prior studies and the ratio of genetic to interaction variance has been large in all instances (Fort et al, 1996;Larson and Shaw, 1995;Shaw and Larson, 1996). Therefore, the existence of variance conferring specific adaptation to individual soil fumigation environments for RAS is atypical.…”
Section: Resultsmentioning
confidence: 99%
“…Some information about genetic × fumigation interactions for root characters might be inferred from evaluation of above-ground traits in fumigation experiments, which indirectly reflect rhizosphere conditions. While substantial genetic variance has been found for many above-ground growth and productivity traits in fumigation studies (Fort et al, 1996;Larson and Shaw, 1995;Shaw and Larson, Deficient root growth or poor root health are known to have negative consequences for strawberry (Fragaria ×ananassa) productivity (Wilhelm and Paulus, 1980;Yuen et al, 1991). Currently, root development and health do not limit commercial production in California because soils are fumigated with a mixture of methyl bromide and chloropicrin before planting, and problems associated with weeds, nematodes, and soilborne fungi are minimized (Himelrick and Dozier, 1991;Wilhelm and Paulus, 1980).…”
mentioning
confidence: 99%
“…Two studies in California that measured leaf number, plant diameter, yield, fruit weight, and fruit appearance on fumigated and nonfumigated soils did not identify any genotypes with strong tolerance to sublethal levels of soil pathogens (Larson and Shaw, 1995;Shaw and Larson, 1996), although a significant interaction between genotype and fumigation was observed in the second study. The authors concluded that lack of fumigation affected all cultivars similarly because the interaction only explained 2% to 5% of the variance.…”
mentioning
confidence: 89%
“…However, only a limited representation of the strawberry germplasm grown in the United States was represented in these studies. Only California genotypes were tested in Larson and Shaw (1995), and in Shaw and Larson (1996), nine California genotypes and nine eastern genotypes were used, six of which were from the U.S. Department of Agriculture program in Maryland.…”
mentioning
confidence: 99%